The Mechanism and Clinical Application of Constraint-Induced Movement Therapy in Stroke Rehabilitation - Wang, Dong; Xiang, Junlu; He, Ying; Yuan, Min; Dong, Li; Ye, Zhenli; Mao, Wei (Frontiers in Behavioral Neuroscience, 2022)
Constraint-induced movement therapy (CIMT) has been widely applied in stroke rehabilitation, and most relevant studies have shown that CIMT helps improve patients’ motor function. In practice, however, principal issues include inconsistent immobilization durations and methods, while incidental issues include a narrow application scope and an emotional impact. Although many studies have explored the possible internal mechanisms of CIMT, a mainstream understanding has not been established.